Evaluasi program Al-Miftah lil Ulum dalam penguatan karakter religious dan budaya akademik santri dengan pendekatan CIPP - Yetri Yetri; Muhammad Hafis Bin Redwan; Elmeki Elmeki; Arifmiboy Arifmiboy (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study is the first to evaluate the implementation of Al-Miftah in Islamic boarding schools in West Sumatra, thus providing a contextual perspective that has not been previously revealed in the literature. The research method used is descriptive qualitative by collecting data through documentation studies (checklists of 6 types of documents), interviews with Islamic boarding school leaders and program coordinators, and analysis of attendance books and memorization checklists volumes 1-3 from 23 first-grade students in the odd semester of 2025/2026. The results of this study indicate that context evaluation supports the preservation of yellow books. Input evaluation reveals trained Sidogiri teachers, a complete syllabus, and a dedicated time allocation. Process evaluation shows high enthusiasm with 100% attendance in 7 meetings. The main obstacle, namely slow memorization of students, is overcome with additional time. Product evaluation shows 100% memorization completion (165 items), the ability to read bare books, and increased discipline, independence, and respect (ta'dzim). The novelty of this research lies in its integration of the CIPP model with authentic Islamic boarding school documentation to measure the effectiveness of the Al-Miftah method in simultaneously shaping religious character and academic culture. This distinguishes it from previous research that focused solely on learning outcomes.